2015
DOI: 10.4149/neo_2015_076
|View full text |Cite
|
Sign up to set email alerts
|

Influence of surgical resection of hepatocellular carcinoma(HCC) for hematogenous dissemination of HCC cells and its effect on recurrence and metastasis: 3 years prospective study

Abstract: Aims was to study whether hepatal surgery leads to hematogenous dissemination of hepatocellular carcinoma (HCC) cells and determine period of its persistence by nested reverse transcription-polymerase chain reaction (RT-PCR).Peripheral vein blood (5ml) samples were obtained from 54 HCC patients of T 1 N 0 M 0 and 6 HCC patients of T 2 N 0 M 0 stage and 20 patients with liver cavernous hemangioma(LCH) before operation and 48h, 72h and 1 week after surgical resection of hepatoma between Janurary 1 st , 2007 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Therefore, the determination of novel prognostic biomarkers is urgently required in order to enhance the prediction of the disease course of HCC at diagnosis. Previous findings have suggested that disorder in co-stimulatory or co-inhibitory signaling pathways serves a critical role in tumor cell evasion of adaptive immune surveillance (2124). In particular, the dysregulation of B7-H2 and/or B7-H3 may deregulate T lymphocyte function in the HCC microenvironment, and even promote recurrence following surgery in patients with HCC (8,15).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the determination of novel prognostic biomarkers is urgently required in order to enhance the prediction of the disease course of HCC at diagnosis. Previous findings have suggested that disorder in co-stimulatory or co-inhibitory signaling pathways serves a critical role in tumor cell evasion of adaptive immune surveillance (2124). In particular, the dysregulation of B7-H2 and/or B7-H3 may deregulate T lymphocyte function in the HCC microenvironment, and even promote recurrence following surgery in patients with HCC (8,15).…”
Section: Discussionmentioning
confidence: 99%
“…AFP is an early warning biomarker for the diagnosis of HCC occurrence. Recently, studies have shown that AFP plays a critical role in HCC cells resistance to anti-tumour drug effects [22, 23] and AFP expression was positively associated with HCC recurrence and metastasis [2426]. These results suggested that AFP overexpression was an important factor for the promotion of HCC cells malignant behaviors.…”
Section: Discussionmentioning
confidence: 98%
“…Nevertheless, HCC patients are typically diagnosed at advanced stages, the majority of whom have suffered extrahepatic metastasis, causing patients to lose the opportunity for surgery or radiofrequency ablation (Colagrande et al, 2016). In addition, early frequent metastasis as well as postsurgical recurrence or metastasis can also result in similar consequences (Liu et al, 2015). Consequently, systemic administration, as an effective countermeasure against metastasis, appears to be crucial in the treatment of HCC patients, especially chemotherapy.…”
Section: Discussionmentioning
confidence: 99%